Puya hamata demography as an indicator of recent fire history in the páramo of el ángel and volcán chiles, ecuador-colombia (2014)
High-altitude páramo grasslands are important for their biodiversity and the ecosystem services that they provide to Andean people, but they are sensitive to disturbances, such as fire. Understanding the ecological impacts of disturbance is critical for the effective management of páramos. Indicator species studies can provide a relatively efficient way to gain such understanding. Puya hamata is a flagship giant rosette plant and has potential as an indicator of recent páramo fire history. To determine population size structure, mortality, recruitment and growth rates of Puya hamata rosettes, all Puya plants in 400 m2 plots were surveyed in 2008 and again one year later. Sixteen plots were recorded in both years, containing exactly 1000 plants. Mortality was very low during this period (0.6%). Only 27 new plants were recruited. Three different size distribution patterns were observed in the plots: (1) low plant numbers across all size ranges; (2) a single dominant peak in numbers at a particular size; (3) two dominant peaks in numbers at distinct sizes. Estimated life span of Puya hamata was 28 years based on growth rates, and growth rate declined beyond the size at which most rosettes reproduce.